Effects of the Built Environment on Pedestrian Accessibility in Neighbourhoods in Southern Chile. The case of Temuco, Chile. Issue 1 (May 2020) - Zumelzu, A; Estrada, M; Jara, C; Peña, C
Abstract: The aim of this article is to evaluate the effects of the built environment on pedestrian accessibility in two neighborhoods in the area of Alemania Avenue, in the city of Temuco, Chile. The methodology integrates three evaluation methods: the method Morpho to explore the morphological conditions that influence walkability; The method developed by Emily Talen to measure walking distance to local services and facilities; and People Following method from Space Syntax theory to evaluate which spatial factors influence the choice of routes and to explore the distance that people walk between their points of interests. Results show that the choice of routes that people take to reach a destination is not defined by the shortest route, but rather by the spatial quality of streets and street frontages. The study suggests that elements such as blind walls, the absence of green spaces and the decrease in the size of sidewalks on streets affects negatively in the choice of routes, and consequently pedestrian accessibility. The article concludes with recommendations for urban planning neighborhoods towards a more sustainable future.